Consideraciones prácticas sobre las cláusulas de ajuste de precio en contratos de compraventa de acciones - De la Piedra Calle, Ricardo (2020)
Price adjustment clauses play a predominant role in stock purchase agreements. Due to their dynamic nature, companies are in constant movement, which complicates the determination of their value and, therefore, their price. Depending on the agreed type of price adjustment, it can shorten the gaps in the valuation of a company between seller and buyer, regulate and mitigate the changes in assets linked to a deferred closure or even a valuation made with outdated financial statements. Being a matter linked to both legal and financial issues, understanding the concepts related to its structuring and execution is fundamental for a transactional lawyer.